Different immunogens and prime-boost vaccination strategies affect the efficacy of recombinant candidate vaccines against pathogenic orthopoxviruses - Antonia Radaelli; Carlo Zanotto; Chiara Brambilla; Tommaso Adami; Francesca Paolini; Aldo Venuti; Adriana Manuka; Irsida Mehmeti; Carlo De Giuli Morghen (Virology Journal)
Highlights Recombinant avipoxviruses as putative recombinant vaccines against MPXV. Different prime–boost regimens to improve immunization against orthopoxviruses. Mucosal and intramuscular immunization to enhance the humoral and neutralizing immune response.